Integrating SiO2 nanoparticles to achieve color uniformity and luminous efficiency enhancement for white light emitting diodes - Phan Xuan Le; Phung Ton That (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
A phosphor structure with SiO2 nanoparticles is proposed to achieve the enhancement in the correlated color temperature (CCT) homogeneity and the luminescence performance for white light-emitting diodes (WLEDs). As SiO2 is integrated into the phosphorus compound, the scattering effect of this material contributes to better blue-light utilization. Thus, this innovative packaging design results in a significant increased lumen efficiency, more than 12%, in comparison with that of conventional dispensing ones. Meanwhile, the angular CCT deviation also decreases considerably, from 522 K to 7 K, between the angles of -70 and 700. Moreover, this reduction leads to the diminishment of yellow ring phenomenon effect. In addition, the measurement of haze demonstrates that there is a strong scattering in the visible spectrum when SiO2 is added into the silicone film. Besides that, when increasing the driving current, SiO2 stabilizes the chromaticity coordinate shift, which is a vital requirement for indoor lighting applications. Furthermore, SiO2 nanoparticles own excellent optical features, cost efficiency, and simple production will probably turn this material into a potential material in advancing the optical performance of WLEDs.